Universalitas Sikap Prososial: Menelusuri Kaitannya dengan Persepsi Multikulturalisme - Johanes, Yotam; Meinarno, Eko Aditiya (Universitas Muria Kudus, 2025)
Prosociality universal application, which transcends the boundaries of social and cultural differences, enabled people to support collective well-being. However, the tendency to limit helping behavior to group interests undermines its universality and does not lead to a harmonious society. The phenomenon of Indonesian society in recent years has shown a trend towards exclusive ingroup support and rejection of outgroup empowerment, especially in Muslim communities in Indonesia. The lackluster outgroup support from the community suggested an underlying problem, which is how people perceive religious diversity in general. The purpose of this study is to determine how attitudes that support diversity promotion relate to how social norms about diversity are perceived. The Normative Multiculturalism Scale and Prosocial Attitudes toward Out-group measures were completed by 81 Muslim individuals through an online survey. Correlational analysis was conducted by examining the relationship between the dimensions of Normative Multiculturalism and Prosocial Attitudes towards the Out-group. The results showed significant positive correlations on each dimension of Normative Multiculturalism. Pengaplikasian perilaku menolong yang melewati batas-batas perbedaan sosial dan budaya, memampukan manusia mencapai kesejahteraan kolektif. Namun, kecenderungan membatasi perilaku menolong untuk kepentingan kelompok, menggagalkan prinsip keuniversalannya dan tidak mewujudkan kehidupan masyarakat yang harmonis. Fenomena kehidupan masyarakat Indonesia dalam beberapa tahun terakhir menunjukkan tren pada pembatasan sikap dukungan yang eksklusif pada ingroup dan sikap penolakan pemberdayaan outgroup, khususnya pada masyarakat Muslim di Indonesia. Rendahnya sikap dukungan masyarakat terhadap out-group mengusulkan masalah yang lebih mendasar, yaitu persepsi terhadap keberagaman agama. Penelitian ini bertujuan untuk mengidentifikasi hubungan persepsi norma sosial terhadap keberagaman dengan sikap dukungan terhadap promosi keberagaman. Pengukuran Multikulturalisme Normatif dan Sikap Prososial terhadap Out-group diselesaikan oleh 81 Muslim melalui survei online. Analisis korelasional dilakukan dengan menguji hubungan dimensi Multikulturalisme Normatif dengan Sikap Prososial terhadap Out-group. Hasil menunjukkan korelasi positif yang signifikan pada setiap dimensi Multikulturalisme Normatif.